A Phospholipid Transfer Protein: The link between lipid metabolism and inflammation in healthy pregnancy and pregnancy with cardiometabolic complications: Phospholipid Transfer Protein in pregnancy - Stefanović, Aleksandra (Journal of Medical Biochemistry, 2026)
Background: Phospholipid transfer protein (PLTP) regulates high density lipoprotein (HDL) remodelling by transferring cholesterol and phospholipids and affecting particle size and function. Pregnancy alters lipid metabolism, but the adaptation of PLTP to pregnancy remains poorly understood. This study investigated longitudinal changes in PLTP gene expression and concentration through healthy pregnancy and pregnancy with cardiometabolic complications, as well as their associations with maternal lipid metabolism and inflammatory status. Methods: We followed 84 healthy and 20 pregnant women who developed gestational diabetes mellitus and hypertensive disorders during pregnancy. PLTP gene expression, PLTP concentration, advanced lipid profile parameters and inflammatory status were analyzed throughout trimesters. Results: A comparable trajectory of changes in PLTP gene expression and PLTP concentrations was observed in both groups, but PLTP gene expression in the first trimester was significantly lower in the group with complications (p < 0.05). Analysis of serum non-cholesterol sterols in HDL subfractions (NCSHDL) and plasma ceramides [ceramide C16:0 (Cer C16:0), ceramide C24:0 (Cer C24:0)], has revealed significantly lower desmosterolHDL (p < 0.05), while significantly higher C24:0 (p < 0.001) concentrations in the group with complications in the first trimester. Higher levels of resistin (p < 0.05) were found in the first trimester in the group with complications. PLTP gene expression in the first trimester was independently associated with pregnancy complications. Conclusions: Our results showed altered PLTP gene expression, advanced lipid profile, and inflammatory status in the first trimester of pregnancy with cardiometabolic complications. Our findings emphasize the importance of a thorough investigation of lipid metabolism and inflammatory pathways in early pregnancy to improve the outcomes.